OPTIMIZING TECHNOLOGY-BASED TRAINING TO IMPROVE THE PERFORMANCE OF VOCATIONAL TRAINING INSTITUTE MEMBERS - Butarbutar, Marisi; Efendi, Efendi; Ramadhan, Mhd; Simatupang, Sudung; Nainggolan, Anju Bherna D (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
Abstract. This study aims to analyze the optimization of technology-based training to improve the performance of members of vocational training institutions. The research method is descriptive qualitative method with data collection of interviews, observations, literature studies. Data were analyzed by thematic analysis. The results showed that not all dimensions of technology-based training were optimized by the institution in improving the performance of its members. To optimize technology-based training requires continuous member assistance during training, reviewing training programs by involving members, investing in technology-based training facilities and infrastructure, and collaborating with related parties.